the The Effect of Murotal Al-Qur’an Therapy Againt Anxiety Level of Hemodialysis Patients at X Tangerang Hospital: Hemodialisa:,Kecemasan;,Murotal AL-Qur’an - Febriyanti, Hana (Sekolah Tinggi Ilmu Kesehatan RS Husada, 2024)
Introduction: Hypertension is one of the most common causes of death worldwide, and it is a non-communicable disease that is a major health problem. In adolescence, around 70% of hypertension cases are primary hypertension, which begins with a pre-hypertensive condition that continues into adulthood and carries a risk of morbidity. The objective of this study is to determine the correlation between lifestyle and hypertension in adolescents. Method: This quantitative research uses a cross-sectional approach. A total of 2,007 individuals were sampled using the purposive sampling method. A digital sphygmomanometer and questionnaire sheet were used to collect data. The chi equation is used in data analysis. Results: The study's findings indicate that there is a relationship between lifestyle and cases of hypertension in adolescents. Based on the chi-square statistical test results, the P value is 0.000 (? = 0.05), and the P value is 0.05, which indicates that there is a relationship between lifestyle and cases of hypertension in adolescents. Conclusion: According to the results of the chi-square statistical test, there was a relationship between lifestyle and the incidence of hypertension in adolescents in the Kiajaran Wetan Community Health Center Work Area. P value = 0.000 (? = 0.05). In the villages supported by the Kiajaran Wetan Community Health Center, health workers must carry out a comprehensive youth posyandu.